An overview of sprouts nutritional properties, pathogens and decontamination technologies. (April 2021) - Mir, Shabir Ahmad; Farooq, Saqib; Shah, Manzoor Ahmad; Sofi, Sajad Ahmad; Dar, B.N.; Hamdani, Afshan Mumtaz; Mousavi Khaneghah, Amin
Abstract: Sprouts are the germinated seeds of herbaceous plants, rich sources of health-promoting bioactive compounds, vitamins, and minerals compared to the adult edible plant parts. Sprouts are gaining popularity among consumers. However, numerous foodborne outbreaks associated with the consumption of sprouts are a matter of concern. Therefore, various decontamination techniques have been exploited to control or eliminate the pathogens responsible for sprouting contamination. However, based on consumer preference, the related industries are always trying to approach the technology with the least effect on the germination or sprouting properties while keeping in mind the safety and quality of products as well. Moreover, technologies are also selected based on the minimal effect on nutritional and sensory properties and extend shelf life sprouts. In this review, the nutritional properties, pathogenic prevalence among sprouts as well as some of the newly introduced techniques for their decontamination besides the associated challenges and perspectives were addressed. Graphical abstract: Image 1 Highlights: Sprouting leads to the significant change in the nutritional profile and bioactive compounds of germinated seeds. Considerable increase in foodborne outbreaks posses the challenge to industry associated with the production of sprouts. Chemical treatment is a cost-effective method for the decontamination of sprouts. Non-thermal technologies have shown promising applications by improving the safety and quality of sprouts.